1991
DOI: 10.1161/01.res.69.5.1301
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis in the excitability of isolated guinea pig ventricular myocytes.

Abstract: Hysteresis phenomena were demonstrated in the excitability of single, enzymatically dissociated guinea pig ventricular myocytes. Membrane potentials were recorded with patch pipettes in the whole-cell current-clamp configuration. Repetitive stimulation with depolarizing current pulses of constant cycle length and duration but varying strength led to predictable excitation (1:1) and nonexcitation (1: 0) patterns depending on current strength. However, transition between patterns depended on the direction of cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This means that threshold potential may shift to more negative values, thus increasing hysteresis of excitability. 13 It is important to point out that, in spite of the slow time course of the decrease in Q0 (Figure 3), changes in the I-V relation already are apparent after trains of only five voltage-clamp pulses. This explains why, under current-clamp conditions, a short train of action potentials may be sufficient to alter the excitability as the cell is shifted from its quiescent to its active state.…”
Section: Implications On Cell Excitabilitymentioning
confidence: 90%
“…This means that threshold potential may shift to more negative values, thus increasing hysteresis of excitability. 13 It is important to point out that, in spite of the slow time course of the decrease in Q0 (Figure 3), changes in the I-V relation already are apparent after trains of only five voltage-clamp pulses. This explains why, under current-clamp conditions, a short train of action potentials may be sufficient to alter the excitability as the cell is shifted from its quiescent to its active state.…”
Section: Implications On Cell Excitabilitymentioning
confidence: 90%
“…These transients indicate the presence of processes with long time constants. It is thus possible that including effects extending over several beats that are not presently incorporated into the ionic model ͑e.g., pumps, exchangers, time-varying ionic concentrations͒ or into the simple one-dimensional map ͑e.g., memory of excitability and APD͒ 14,36,40,41,45,46,[60][61][62] might replicate such long transients. However, there are practical experimental difficulties ͑e.g., rundown of currents͒ inherent in sorting out these slow phenomena in the single-cell preparation.…”
Section: H Slow Transients and Memorymentioning
confidence: 98%
“…13 There is also amplitude hysteresis in the threshold for ''capture'' when an electronic pacemaker is inserted into a patient: i.e., the threshold current is slightly higher when stimulus amplitude is increased slowly from a subthreshold value than when it is decreased from a suprathreshold value. 64 While it has been suggested that the decreased threshold found when slowly decreasing stimulus amplitude during 1:1 rhythm is due to the higher coronary blood flow then present, 64 this ͕1:1↔1:0͖ hysteresis can also be seen in isolated slow-response rabbit atrium ͑where it has been termed ''excitation hysteresis''͒, 60 isolated papillary muscle, 46 single guinea-pig ventricular cells, 61 a modified version of the LR model, 62 an ''analytic'' model, 61 and a differential-difference model. 46 In sheep papillary muscle, 65 as well as in the modified version of the LR model, 62 injection of an additional stimulus ͑which is, however, subthreshold͒ during 1:1 rhythm can produce the ͕1:1→1:0͖ flip; an additional suprathreshold stimulus delivered during 1:0 rhythm can produce the ͕1:0→1:1͖ flip in the model.…”
Section: J Other Forms Of Bistability In Cardiac Electrophysiologymentioning
confidence: 99%
“…We have often observed that the resting potential of the myocyte shifts slightly (within 2 mV) during control recordings, particularly when the cell is paced repetitively at a relatively short ( < 1 s) cycle length (Lorente et al, 1991). Thus, for the control runs, we always adjusted the holding potential at the onset of recording to match (within 1 mV) the value of resting potential that was measured immediately before switching to voltage clamp mode.…”
Section: Action Potential Clampmentioning
confidence: 99%